2014
DOI: 10.1016/j.ygyno.2014.02.030
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of prophylactic salpingectomy with delayed oophorectomy as risk-reducing surgery among BRCA mutation carriers

Abstract: OBJECTIVE Given emerging evidence for the fimbria as the site of origin for many serous carcinomas in BRCA mutation carriers, consideration is being given to studying prophylactic salpingectomy with delayed oophorectomy (PSDO) as risk-reducing surgery. We aimed to determine the interest in a study of PSDO among these women. METHODS We evaluated the results of an online survey conducted by Facing Our Risk of Cancer Empowered (FORCE), a patient advocacy group, from October 2010 to August 2012. Premenopausal BR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
65
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 30 publications
0
65
0
1
Order By: Relevance
“…[34,43,44] The top ranked barrier was lack of evidence of level of risk benefit obtained from RRS. While the tube is an extremely important piece of the puzzle, it does not explain the entire picture.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[34,43,44] The top ranked barrier was lack of evidence of level of risk benefit obtained from RRS. While the tube is an extremely important piece of the puzzle, it does not explain the entire picture.…”
Section: Methodsmentioning
confidence: 99%
“…Of note, two-thirds of BRCA carriers in a study from the USA found the risks associated with the need for two surgeries, possibility of not lowering ovarian cancer risk, and potential disruption of ovarian blood supply to be acceptable. [44] There is need to understand the views of high risk women in the UK too.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Salpingectomy with delayed oophorectomy has been proposed as an alternative to RRSO in order to postpone the onset of premature menopause and its effect on non-cancer menopause-related morbidity and quality of life(116). Modeling of the cost-effectiveness of this approach demonstrated acceptability and a survey of previvors and key stakeholders demonstrated interest and acceptability of this approach (117, 118). Several prospective studies are in various phases of development and patient accrual (119, 120).…”
Section: Surgical Prevention For Women At High Risk Of Ovarian Cancermentioning
confidence: 96%
“…However, even if prophylactic salpingectomy proves to provide optimal gynaecologic cancer risk reduction, preservation of the ovaries will not confer the same breast cancer risk reduction and should be factored into patient counselling. In a study looking at acceptability of prophylactic salpingectomy with delayed oophorectomy, the patient's primary concerns in participation were related to surgical complications, ovarian damage and costs [11].…”
Section: The Landscape Of Prevention: Oral Contraceptive Pills Tamoxmentioning
confidence: 99%